Revision of Nanophareus, a mysterious harvestman genus from Chile, with descriptions of three new species (Opiliones: Laniatores: Gonyleptidae) - Hara, Marcos Ryotaro; Pinto-Da-Rocha, Ricardo; Kury, Adriano Brilhante (Zootaxa, 2012)
The Chilean genus Nanophareus Roewer, 1929 is revised and three new species are described: N. araucanus sp. nov. (typelocality: Parque Nacional La Campana, Valparaíso, Chile); N. bipartitus sp. nov. (type locality: Parque Nacional La Cam-pana, Valparaíso, Chile); N. bosqenublado sp. nov. (type locality: Parque Nacional Fray Jorge, Coquimbo, Chile). Thetype species, N. palpalis Roewer, 1929, is redescribed and a lectotype is designated. A cladistic analysis was performedusing these three new species plus N. palpalis and 14 more laniatorid species, and a data matrix of 72 characters: Sevenfrom the ocularium, 22 from the dorsal scutum, one from the venter, one from the chelicera, eight from the pedipalp, 24from male legs, and nine from male genitalia. Two equally most parsimonious trees were found (L = 210; C.I. = 0.41; R.I.= 0.51). Nanophareus was recovered as nested within a paraphyletic subfamily Pachylinae. The genus Nanophareus wasfound to be monophyletic based on the following exclusive synapomorphies: An external row of enlarged tubercles in-serted among small ones on lateral margin of the dorsal scutum (innapplicable in N. bosqenublado); the ventro-basal mar-gin of pedipalpal tibia curved 90 degrees in lateral view; and retrolateral seta of the pedipalpal tibia with a socket apically bifid (socket and seta longer than pedipalpal tibia length).